2013
DOI: 10.1128/mcb.01213-12
|View full text |Cite
|
Sign up to set email alerts
|

The Corepressor CTBP2 Is a Coactivator of Retinoic Acid Receptor/Retinoid X Receptor in Retinoic Acid Signaling

Abstract: Retinoids play key roles in development, differentiation, and homeostasis through regulation of specific target genes by the retinoic acid receptor/retinoid X receptor (RAR/RXR) nuclear receptor complex. Corepressors and coactivators contribute to its transcriptional control by creating the appropriate chromatin environment, but the precise composition of these nuclear receptor complexes remains to be elucidated. Using an RNA interference-based genetic screen in mouse F9 cells, we identified the transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…The three latter genes are involved in retinoic acid signaling pathway regulation and are considered as essential for diaphragm development. Interestingly, CTBP2 has been shown as a potent coactivator of retinoic acid signaling pathway, which is a major pathway for diaphragm development . This is achieved through recruitment of p300/CREBBP histone acetyltransferases onto retinoic acid target genes promoters, creating a permissive chromatin environment for their transcription …”
Section: Discussionmentioning
confidence: 99%
“…The three latter genes are involved in retinoic acid signaling pathway regulation and are considered as essential for diaphragm development. Interestingly, CTBP2 has been shown as a potent coactivator of retinoic acid signaling pathway, which is a major pathway for diaphragm development . This is achieved through recruitment of p300/CREBBP histone acetyltransferases onto retinoic acid target genes promoters, creating a permissive chromatin environment for their transcription …”
Section: Discussionmentioning
confidence: 99%
“…Enriched CtBP2 expression has been reported in stem cells, and this protein has been demonstrated to have an important role in stem cell maintenance and the regulation of differentiation in ESCs [66]. CtBP2 has also been identified as a coactivator that is critical for retinoic acid (RA)-induced transcription in mouse F9 cells [67]. CtBP1 and CtBP2 have been reported to directly interact with PRDM16 and selectively mediate the repression [68].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms of resistance to RA have been described to date, including mutations in the ligandbinding domain of PML-RARa in APL patients (17) and the epigenetic silencing of the RARb receptor (18,19), which leads to the inability of RA to activate the pathway and hence to RA resistance. CTBP2, generally a corepressor protein, was identified as a positive cofactor of RAR-RXR in mouse F9 cells, and its suppression conferred resistance to RA (13). Using loss-offunction genetic screens Huang and colleagues showed that knockdown of the zinc finger protein ZNF423 leads to the loss of activation of RA target genes.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of RA, RAR/RXR is in complex with corepressors like NCoR, SMRT, and HDACs that repress the transcription of RA target genes (9,10). Binding of RA to RAR results in a conformational change of RAR, which leads to an exchange of repressor proteins for transcriptional coactivator proteins like CBP/p300, PCAF, CTBP2, and p160, enabling the transcription of RA target genes (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%